EFFECT OF FATTY ACID BASED FUNCTIONAL LIPIDOMICS IN WOMEN WITH BREAST CANCER - PREETHIKA A; SUCHETHA KUMARI N (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Lipid metabolism alteration is a prominent feature during malignant transformation. We investigated the difference in plasma fatty acids (FAs) and molecular biomarkers in breast cancer women and controls. Methods: This comparative study was carried out on eighty breast cancer women and forty control women. FAs were analyzed in gas chromatography and calculated as a percentage of total FAs. FA molecular markers were estimated by the FA data. Non-parametric statistical tests were used. Results: Saturated FAs were higher in the case group. Control group had higher linoleic acid (p=0.04), suggesting decreased desaturase activity. N-6 FAs were higher and n-3 FAs were lower in breast cancer cases. The n6/n3 ratio, cardiovascular risk ratio (p<0.001), and inflammatory risk ratio were high, whereas saturation index and unsaturation index (p=0.05) were lower in breast cancer cases. Conclusion: Lipidomics of the cell membrane is significantly influenced by FAs, and the dietary FAs regulate the enzymatic activities in the FA metabolism pathway.